Heavy Metal Accumulation in Maize (Zea mays L.) Grown on Chromated Copper Arsenate (CCA) Contaminated Soil Amended with Treated Composted Sewage Biosolid - Nakiguli, C. K.; Namakula, B.; Odda, J.; Wasswa, J.; Ntambi, E. (Journal of Environmental Protection, 2018)
A pot experiment was conducted to investigate the heavy metal accumulation in maize ( Zea mays L.) plant grown in chromated copper arsenate (CCA) soil amended with treated composted sewage biosolid. The initial concentrations of chromium, copper, arsenate in the CCA soil and sewage biosolid were determined by atomic absorption spectrophotometer. These were found to be, in CCA soil: 365.8 ± 6.18, 109.22 ± 14.04, 28.22 ± 3.8 and in sewage biosolid: 35 ± 1.06, 1.0 ± 0.02, 0 mg∙kg−1 respectively. The concentration of Cr, Cu and As determined in both the roots and shoots generally decreased with increase in percentage amendment concentration and number of days (20 and 40 days after planting). At 20 days, the total metal concentration ranges in roots were as (5.54 ± 0.03 - 6.69 ± 1.14), Cr (9.59 ± 0.02 - 13.22 ± 0.03), Cu (2.28 ± 0.06 - 4.53 ± 0.37) mg∙kg−1 while at 40 days the values were As (5.60 ± 0.19 - 6.08 ± 0.01), Cr (9.47 ± 0.04 - 10.95 ± 0.09), Cu (3.94 ± 0.19 - 4.64 ± 0.07) mg∙kg−1. For the shoot system, the concentrations of the metals at 20 days were as (5.28 ± 0.03 - 5.90 ± 0.13), Cr (9.30 ± 0.05 - 10.07 ± 0.06), Cu (3.64 ± 0.12 - 4.72 ± 0.15) mg/kg while at 40 days the values obtained were as (5.28 ± 0.03 - 5.9 ± 0.13), Cr (9.69 ± 0.14 - 10.07 ± 0.03), Cu (2.94 ± 0.72 - 4.53 ± 0.03) mg∙kg−1. The roots accumulated the three heavy metals more than the shoot system at all treatments used. Concentration of arsenic, chromium and copper in the plants decreased with increasing percentage amendments. The results suggest relatively low bioavailability of the three metals in CCA soil treated with high percentages of sewage biosolid as an amendment. How
Keywords: Arsenic; Chromium Copper; Contaminated CCA Soil; Sewage Amendment